Quality and safety of maize (Zea mays L.) from Rondônia state storage units, Northern Brazil. Issue 1 (2nd January 2018) - Valmorbida, Roberta; Savi, Geovana D.; Silva, Juliana R.; Yanez, Monica M.O.; Soares, Carlos E.S.; Runtzel, Cristina; Nascimento, Priscila N.; Scussel, Vildes M.
ABSTRACT: The quality and safety of maize ( Zea mays L.) from different grain storage units (GSUs), located in the main producing region of Rondônia State, Northern Brazil, were evaluated. Maize grains ( n = 76) stored in four GSUs were collected from July to November 2014 and evaluated for grain damages, humidity, fungi and fumonisins (FBs) content. The climate conditions data were also obtained from plant growing to storage periods. Regarding the moisture content and water activity (aw ), these varied from 10.0% to 16.1% and 0.5 to 0.8, respectively. As expected, fungi spores were present in 94.8% of the samples, prevailing Fusarium genera, with a fungi colony maximum of 2.2 × 10 4 CFU g −1 . Regarding FBs, 60.5% of the samples were contaminated, below Brazilian and United States maximum limits, but 9.2% had levels higher than the European legislation.